Pengaruh Konsentrasi Mikroplastik terhadap Aktivitas Enzim Antioksidan dan Pertumbuhan Chlorella vulgaris dalam Sistem Kultur Terkontrol - Dewi Kartika Sari; Ahmad Rahman (Lembaga Publikasi Ilmiah Nusantara, 2026)
The increasing accumulation of microplastics in aquatic environments poses a significant threat to photosynthetic organisms, including the microalga Chlorella vulgaris. This study aims to analyze the effects of varying microplastic concentrations on antioxidant enzyme activity and growth of C. vulgaris under controlled culture conditions. The experiment applied environmentally relevant and sub-lethal concentrations of microplastics. Observed parameters included growth rate, chlorophyll content, and antioxidant enzyme activities such as superoxide dismutase (SOD) and catalase (CAT). The results show that increasing microplastic concentrations reduced growth rate by more than 35% at higher exposure levels and significantly elevated antioxidant enzyme activity as a response to oxidative stress. SOD and CAT activities increased by approximately 1.8–2.3 times compared to the control, indicating the accumulation of reactive oxygen species. In addition, microplastics disrupted photosynthetic processes and cellular energy metabolism. These findings demonstrate that microplastics act as environmental stressors that trigger physiological and biochemical responses in C. vulgaris. This study highlights the importance of assessing microplastic risks to primary producers in aquatic ecosystems and their implications for food web stability.